2021
DOI: 10.1177/15910199211069259
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30-day mortality after endovascular thrombectomy for large vessel occlusion in the elderly

Abstract: Objectives Elderly acute ischemic stroke (AIS) patients (≥80 years) would have dismal clinical outcomes even after successful endovascular revascularization for large vessel occlusion (LVO) in the anterior circulation. We aimed to identify predictors of 30-day mortality after endovascular thrombectomy (EVT) in the elderly. Materials and Methods We included older patients who underwent EVT for AIS due to LVO within 6 h after stroke onset in the anterior circulation between 2017 and 2019. Patients due to posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…The authors found that the type of technique for thrombectomy was not associated with an increased likelihood of death at 30 days post stroke. Our results are in line with the study of Lai et al as we showed that the type of thrombectomy technique is not associated with risk of death after EVT [ 11 ]. However, in our sample of 105 patients aged 80 years or older we investigated not only the predictors of 90-day mortality, but also those of functional independence at 3 months, successful reperfusion (mTICI ≥ 2b) and haemorrhagic transformation.…”
Section: Discussionsupporting
confidence: 93%
“…The authors found that the type of technique for thrombectomy was not associated with an increased likelihood of death at 30 days post stroke. Our results are in line with the study of Lai et al as we showed that the type of thrombectomy technique is not associated with risk of death after EVT [ 11 ]. However, in our sample of 105 patients aged 80 years or older we investigated not only the predictors of 90-day mortality, but also those of functional independence at 3 months, successful reperfusion (mTICI ≥ 2b) and haemorrhagic transformation.…”
Section: Discussionsupporting
confidence: 93%
“…Sixth, mean platelet volume/platelet count ratio in patients with large-artery atherosclerosis also is reported to be associated with patient outcome, 34 but unfortunately the SKIP study did not have such data. Seventh, collaterals were also reported to be related to be associated with patient outcome 35,36 but were not fully examined in this study.…”
Section: Discussionmentioning
confidence: 88%
“…Among patients with available follow-up data, mortality rates were 26% and 33% at 30-days and 90-days post DC, respectively. Some published studies report mortality rate ranging from 31 to 37% for patients who are 80 years and older with EVT [11][12][13] although this rate is higher than those for younger patients. McDonough et al compared mortality rate for patients >=85 years old demonstrating better mortality rate of 31% with EVT compared to 54.3% for those received standard of care [11].…”
Section: Discussionmentioning
confidence: 98%